2013
DOI: 10.1002/pssb.201248378
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic approach to the magnetoelectric effect in R Mn2 O5

Abstract: The multiferroic behavior of rare‐earth manganites is studied within a microscopic model including a symmetry‐allowed magnetoelectric coupling between polarization and magnetization. The magnetic subsystem is described by a frustrated Heisenberg spin model, whereas the ferroelectric subsystem is characterized by an Ising model in a transverse field. Using Green's function method we find analytically the temperature and wave vector dependent elementary excitation of the magnetoelectric system, the polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…This shows the importance of the anharmonic spin-phonon interaction and that it must be taken into account in order to obtain correct results. We have observed a similar kink in the temperature dependence of the magnetization in the multiferroic RMn 2 O 5 [27],…”
Section: Numerical Results and Discussionsupporting
confidence: 69%
“…This shows the importance of the anharmonic spin-phonon interaction and that it must be taken into account in order to obtain correct results. We have observed a similar kink in the temperature dependence of the magnetization in the multiferroic RMn 2 O 5 [27],…”
Section: Numerical Results and Discussionsupporting
confidence: 69%
“…There has been increasing recent interest in ME multiferroics , which are materials that show spontaneous magnetic and electric ordering in the same phase. In many papers, the electric properties in multiferroic EuTiO 3 , type‐I multiferroics , BFO , hexagonal h‐ R MnO 3 compounds , R Mn 2 O 5 , and composite multiferroic thin films are studied using the Transverse Ising model (TIM) with S = 1/2. This is reasonable, for example, in the case of h‐ R MnO 3 and R Mn 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This polarization is a consequence of the inverse DM mechanism and is calculated using Eq. (7). In Fig.…”
mentioning
confidence: 98%
“…In accordance with () we have extrapolated the value for g by assuming that the Curie temperature is much higher as TN, for example, TC is of the order of 100K. The parameter g is also selected in agreement with former studies , where we have shown that an enhancement of g leads to an increasing magnetization. The value for J is likewise adopted using this extrapolated TC for the sublattice polarization.…”
Section: Resultsmentioning
confidence: 79%